A needs-supportive intervention to help PE teachers enhance students’ prosocial behavior diminish antisocial behavior - Cheon, S.; Reeve, J.; Ntoumanis, Nikos (Elsevier BV, 2018)
Objectives: Grounded in self-determination theory's dual-process model, we implemented an autonomy-supportive intervention program (ASIP) to help physical education (PE) teachers become more autonomy-supportive and less controlling toward their students. We tested whether such changes in teachers' classroom motivating styles could promote students' prosocial behaviors and diminish their antisocial behaviors. Design: We used an experimental research design to manipulate teachers' motivating style and a three-wave longitudinal design to assess the student-reported dependent measures. Method: We randomly assigned secondary-grade PE teachers (8 women, 25 men) to participate or not in the ASIP. At mid-semester, classroom observers rated teachers' autonomy-supportive and controlling instructional behaviors. At the end of the semester, teachers rated their students' prosocial and antisocial behaviors. At the beginning, middle, and end of the semester, the 1824 students of these teachers completed measures of need satisfaction, need frustration, prosocial behavior, and antisocial behavior. Results: ASIP participation increased teachers' autonomy support and students' need satisfaction and prosocial behavior, and it decreased teachers' control and students' need frustration, antisocial behavior, and attitude toward cheating. Multilevel structural equation modeling showed that longitudinal increases in prosocial behavior were mostly a function of need satisfaction gains while longitudinally decreases in antisocial behavior and acceptance of cheating were mostly a function of need frustration declines. Conclusion: ASIP-enabled benefits extend beyond previously-documented student personal functioning gains (e.g., engagement) to include student social functioning gains as well.